2019
DOI: 10.1111/psyp.13378
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic correlates of lifetime suicidal thoughts and behaviors among adolescents with a history of depression

Abstract: Suicidal thoughts and behaviors (STBs) have been associated with emotion dysregulation and atypical responses to affective and stressful stimuli. To investigate the psychophysiology involved, we measured changes in respiratory sinus arrhythmia (RSA) and cardiac pre‐ejection period (PEP; indexing parasympathetic and sympathetic functioning, respectively) in response to stressful‐ and sadness‐eliciting laboratory probes. Our sample included adolescents with a history of depression and STBs (n = 177), adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 77 publications
(114 reference statements)
0
8
0
Order By: Relevance
“…An experimenter stood next to the participants to ensure that they completed the task correctly and were instructed to complete as many of the puzzles as possible within the 6-minutes. Unsolvable puzzle tasks have the fundamental principles of stress, including novelty, unpredictability and negative feedback are frequently used in stress literature (Perry, Calkins, Nelson, Leerkes, & Marcovitch, 2012;Yang et al, 2019). For a full description including diagrams of puzzles used, see Bibbey (2015).…”
Section: Puzzle Taskmentioning
confidence: 99%
“…An experimenter stood next to the participants to ensure that they completed the task correctly and were instructed to complete as many of the puzzles as possible within the 6-minutes. Unsolvable puzzle tasks have the fundamental principles of stress, including novelty, unpredictability and negative feedback are frequently used in stress literature (Perry, Calkins, Nelson, Leerkes, & Marcovitch, 2012;Yang et al, 2019). For a full description including diagrams of puzzles used, see Bibbey (2015).…”
Section: Puzzle Taskmentioning
confidence: 99%
“…Consistent with these findings, one of the two studies only included in the qualitative synthesis found that adolescents who displayed a decrease in suicidality over time displayed an increase in HRV at rest during night-time, but not during the day (Sheridan et al, 2021), whereas the other study found no group differences on RSA or PEP (Yang et al, 2019).…”
Section: Cardiac Measuresmentioning
confidence: 56%
“…Cross-study heterogeneity was significant (Q = 39.638; p = 0.023), while funnel plot asymmetry was not detected (Kendall's tau = −0.1510, p = 0.2927; Figure S1). Consistent with these findings, one of the three studies included in the qualitative synthesis found that adolescents who displayed a decrease in suicidality over time showed an increase in HRV at rest during night-time, but not during the day (Sheridan et al, 2021), whereas the other study found no group differences on RSA or PEP (Yang et al, 2019). Koenig et al (2018) reported results of a 1-year follow-up assessment of a sample of adolescent girls, for which they reported baseline data in Koenig, Rinnewitz, Parzer, et al (2017).…”
Section: Cardiac Measuresmentioning
confidence: 71%